The effects of spatial dynamics on a wormhole throat - Alias, Anuar; Wan Abdullah, Wan Ahmad Tajuddin (World Scientific Publishing, 2018)
Previous studies on dynamic wormholes were focused on the dynamics of the wormhole itself, be it either rotating or evolutionary in character and also in various frameworks from classical to braneworld cosmological models. In this work, we modeled a dynamic factor that represents the spatial dynamics in terms of spacetime expansion and contraction surrounding the wormhole itself. Using an RS2-based braneworld cosmological model, we modified the spacetime metric of Wong and subsequently employed the method of Bronnikov, where it is observed that a traversable wormhole is easier to exist in an expanding brane universe, however it is difficult to exist in a contracting brane universe due to stress-energy tensors requirement. This model of spatial dynamic factor affecting the wormhole throat can also be applied on the cyclic or the bounce universe model.